(untitled) (Research, Society and Development, 2021)
The pandemic due to the rapid contamination of the Covid-19 virus directly affected sectors of society, which had to adapt to new ways in their lifestyles, mainly in limiting face-to-face social contacts. In the school environment it was no different, regardless of the age group, all students were forced to leave the classrooms, requiring the teaching-learning process to be grounded through the development of new strategies. In this context, the importance of the professional of speech-language pathology education, which is responsible for providing support to parents and teachers, especially with regard to children who have a speech and language problem, for example, and which significantly compromises their learning. to understand how the educational speech therapist shouldperform in Covid-19 pandemic times. The main objective of this research is to analyze how speech therapists canact in the educational process in Covid-19 pandemictimes, which obligatorily removed the students from the classroom. Among the specific objectives: to verify students’ problems in the teaching-learning process carried out via remote; identify the main programs that can be used by educational speech therapists in support of students and their families and teachers; Understand the main actions developed by educational speech therapists. The research problem consists of the following question: how can speech therapists in times of the pandemic of Covid-19 act in favor of theeducational development of students who are outside the school environment? It was found through the research that the performance of the speech therapist is indispensable for the teaching-learning process, because without the proper support of these professionals to children who have problems in aspects of language, it makes even more difficult the educational development of these students who are abroad classrooms.